Socio-economic and Household Characteristics Associated with Work-Family Conflict among Female Primary School Teachers in Enugu State, Nigeria - Uju Nnubia; Vivienne Ibeanu; Franca Okechukwu (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2022)
This study focused on the socio-economic and household characteristics associated with work-family conflict among female primary school teachers in Enugu state, Nigeria. Cross-sectional and correlational study design were used to collect data from 2428 female primary school teachers in Enugu state, Nigeria. Structured questionnaire was used to obtain data on socio-economic and household characteristics, while Work and Family Conflict Scale was used to assess work-family conflict in the dimensions of work to family, family to work and overall work and family interference. Analyses were performed using IBM-SPSS version 23 software. Descriptive data were presented as frequencies and percentages, while Chi square was used to test the hypotheses at p < 0.05. Result showed that 23% of the respondents experienced work-family conflict with higher rate (29.9%) of work to family conflict than 25.1% of family to work conflict.  Higher salary, urban location, living in ≥ 2-bedroom apartment and using communal toilet and bathroom at home were socio-economic factors significantly (p < 0.05) associated with increase in all the dimensions of work-family conflict. On the other hand, household characteristics associated with higher work-family conflict include; having dependent children, age of oldest child > 12 years old, caring for chronically ill family members, and uneasy accessibility of household water supply. Caring for the elderly and having house helps were associated with increased work to family conflict while household size was not found a factor in any dimension of work-family conflict.